KAJIAN KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJAAN PEMBANGUNAN BENDUNGAN KRUENG KEUREUTO DI KABUPATEN ACEH UTARA - Helmi Helmi; Alfiansyah Yulianur; Ella Meilianda (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2016)
Abstract: The implementation of occupational safety and health program is one of the efforts to create a workplace that is safe, healthy and free from environmental pollution, so as to prevent or reduce rather than workplace accidents. The purpose of this research is 1) To determine the level of awareness and understanding of occupational health and safety programs, 2) To find out how the implementation of occupational safety and health program, and 3) To find out what kind of risk of work accidents happened at the project site . The scope of this study is limited to the study of occupational safety and health is applied to the construction of dams Krueng keurueto jobs in North Aceh district. The research was conducted by distributing questionnaires to 65 respondents who were directly involved in the work of this dam. Data processing is performed by analysis of frequency and relative importance index (RII). The object of research is a director of the Company; Project Manager; Field Executive; Field Supervisors and Workers / heavy equipment operator involved in Krueng Dam construction work Keureuto In North Aceh District. Based on the results of data processing and discussion, it has been able to research appropriate research objectives, namely: the level of awareness and understanding of the elements of safety and health programs of work